1999
DOI: 10.4315/0362-028x-62.5.463
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration and Confirmation of Aeromonas hydrophila, Aeromonas caviae, and Aeromonas sobria Isolated from Raw Milk and Other Milk Products in Northern Greece

Abstract: A total of 138 raw cow's and 57 raw ewe's milk samples; 80 pasteurized cow's milk samples; 39 Anthotyros cheese, 36 Manouri cheese, and 23 Feta cheese samples; and 15 rice pudding samples were examined for the presence and any countable population of Aeromonas species. Twenty-two (15.9%) of the 138 cow's milk samples analyzed were contaminated with A. hydrophila. In 13 of these samples, populations of 3.0x10(2) to 5.0x10(3) CFU/ml were counted in starch ampicillin agar (SAA). Eighteen cow's milk samples (13.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 0 publications
6
16
0
4
Order By: Relevance
“…High frequency of Aeromonas in infants and elder were reported by several authors (9,16,22,31). Although not completely understood, this fact has been attributed to intrinsic physiological and immunological characteristics of infants and elder, associated with the presence of Aeromonas in food and beverages (2,18).…”
Section: Resultsmentioning
confidence: 93%
“…High frequency of Aeromonas in infants and elder were reported by several authors (9,16,22,31). Although not completely understood, this fact has been attributed to intrinsic physiological and immunological characteristics of infants and elder, associated with the presence of Aeromonas in food and beverages (2,18).…”
Section: Resultsmentioning
confidence: 93%
“…representatives. Melas, Papageorgiou, and Mantis (1999) examined raw milk and other milk products in Northern Greece and found that A. hydrophila dominated compared to other Aeromonas spp. Villari et al (2000) in a survey study in Italy carried out on ready-to-eat foods (vegetables, cheese, meat products, and ice cream) found that A. hydrophila was the most common isolate from foods of animal origin.…”
Section: Distribution Of a Hydrophilamentioning
confidence: 99%
“…Species of this bacterium are also common in raw milk and other milk products, in particular, Aeromonas hydrophilia, A. caviae, A. sobria, A. veronii, A. salminicida (Papageorgiou et al, 2006;Martins et al, 2002, Melas et al, 1998.…”
Section: Salmonellamentioning
confidence: 98%